HISTORY OF UZBEK NATIONAL FABRICS ATLAS AND ADRAS - Sabina Abdirashidova (Zeta Repository, 2023)
In this article, we will give brief information about the types, weaving and dyeing of our national fabrics "Atlas and Adras", the interest of the countries of the world, ways to preserve our national culture and its importance today.